Analysis of Legal Protection for Employees Who Do Not Have a Fixed-Term Employment Contract (Decision Number 687 K/Pdt.Sus-PHI/2016) - Ekel Tuahta Ginting; Haposan Siallagan; Besty Habeahan (Journal of Legal and Cultural Analytics, 2025)
According to Law No. 13 of 2003 on Manpower, fixed-term employment agreements (PKWT) are not applicable in employment relationships. Employers have ignored the highest time limit allowed by Law Number 13 of 2013 on Manpower regarding the working period of fixed-term contracts. In addition, they still have not fulfilled the rights of time workers such as wages, working hours, and labor social security. This violates the human rights of workers, who as Indonesian citizens are protected by the Indonesian Labor Law. One of the obstacles in the implementation of PKWT according to Law No. 13/2003 lies in two factors. First, the rules governing the implementation of non-permanent contracts are not in line with employment needs. Employers cannot recruit employees for something that is not necessary for the continuity of business operations. Most of the types of work required are fixed and belong to the core work of the production process. Thus, in this case, Article 59 of the Labor Law has been violated, as the work prohibited by the statutory provisions on PKWT